Temperature-Driven Local Acclimatization of Symbiodnium Hosted by the Coral Galaxea fascicularis at Hainan Island, China - Zhou, Guowei; Cai, Lin; Li, Yuanchao; Tong, Haoya; Jiang, Lei; Zhang, Yuyang; Lei, Xinming; Guo, Minglan; Liu, Sheng; Qian, Pei-Yuan; Huang, Hui (Frontiers in Microbiology, 2017)
The success of coral reef ecosystems largely depends on mutualistic symbiosis between scleractinian corals and the dinoﬂagellate photosymbiont Symbiodinium spp.. However, further investigation is needed to elucidate the flexibility of coral-algae associations in response to environmental changes. In this study, we applied a molecular method (high-throughput internal transcribed spacer 2 region of ribosomal RNA gene amplicon sequencing) to explore diversity and flexibility of Symbiodinium associated with Galaxea fascicularis, an ecologically important scleractinian coral species collected at five locations around Hainan Island, South China Sea. The results revealed a high diversity of Symbiodinium subclades with C2r and D17 being dominant in G. fascicularis. Clade D Symbiodinium occurred most frequently in habitats where the annual average sea surface temperatures are highest, suggesting that temperature is an important factor in determining Symbiodinium D compositions in G. fascicularis. The distribution of coral-Symbiodinium associations are possibly mediated by trade-off mechanisms which change the relative abundance of Symbiodinium subclades under different environmental conditions. These findings provide further evidence that reef-building corals such as G. fascicularis can shuffle their symbionts to cope with environmental changes, and have implications for our understanding of the ecology of flexible coral-algal symbiosis.